Peningkatan Pengetahuan Ibu Hamil Melalui Program Mother Smart Grounding (MSG) Dalam Upaya Pencegahan Kejadian Stunting di Klinik Anisa Tabing Kota Padang - Meta Rikandi; Febry Handiny; Asmeri Lamona (STIKes Alifah Padang, 2022)
The prevalence of stunting children in Indonesia is in the high category because based on the 2018 Riskesdas, nationally the prevalence of stunting is 30.8%. (Riskesdas, 2018). Although the incidence of stunting has decreased, according to WHO the percentage is generally still relatively high. The Mother Smart Grounding (MSG) program has the advantage of being a program that focuses on prevention efforts not only for a special group of 1000 HPK, but more for mothers to prepare for their children's growth and development from an early age. In research, moringa can be modified into a variety of healthy snack foods that contain the nutritional needs of both micro and macro nutrients needed for the growth of all groups, especially in toddlers and pregnant women. Therefore, it is necessary to increase the knowledge of pregnant women through the mother smart grounding (MSG) program in an effort to prevent stunting at the Anisa Tabing Padang Clinic in 2019. The results of the community service conducted at the Anisa Clinic showed that 66.67% of mothers' knowledge was in the good category regarding the nutrition of pregnant women, stunting, and the benefits of Moringa leaves for pregnant women. It is hoped that pregnant women can take advantage of Moringa leaves and can consume them as additional food as an effort to prevent stunting in children.